4-Trimethylsilyl-5-iodo-1,2,3-triazole: A Key Precursor for the Divergent Syntheses of 1,5-Disubstituted 1,2,3-Triazoles - Li, Lingjun; Shang, Tongpeng; Ma, Xiaonan; Guo, Haiyun; Zhu, Anlian; Zhang, Guisheng (Synlett, 2015)
Bifunctional 4-trimethylsilyl-5-iodo-1,2,3-triazoles (TMSIT) were reported in this paper, which could be efficiently synthesized directly from readily accessible TMS-alkyne, azide, and copper(I) iodide at room temperature. Using TMSIT as key precursors, a divergent protocol for the preparation of 1,5-disubstituted 1,2,3-triazoles was developed via sequential copper/palladium-catalyzed coupling reactions and desilylation in one pot.
Keywords: alkyne; silyl-1,2,3-triazole; cycloaddition; divergent syntheses; cross-coupling